Estimation of Total Carbon Stocks in Soil and Vegetation of Tropical Peat Forest in Indonesia - Ujang Suwarna; Elias; Istomo (Institut Pertanian Bogor (IPB University), 2012)
The study was conducted in the forest concession area of PT. Diamond Raya Timber, Riau Province, Indonesia. Measurement and calculation carbon stocks in soil and vegetation of tropical peat forest should be done accurately to anticipate carbon trading. The objective of the study is to estimate carbon stocks in soil and vegetation in 4 forest conditions. The study found that biomass and carbon stocks in the soil was 8 times higher than in the vegetation in primary forest condition, and 10 times in logged over forest and secondary forest condition. Carbon stocks in vegetation and soil were 189.45 ton C ha-1 and 1537.37 ton C ha-1 in primary forest, 161.76 ton C ha-1, and 1713.77 ton C ha-1 in logged over area, 139.05 ton C ha-1 and 1486.39 ton C ha-1 in secondary forest, and 43.09 ton C ha-1 and 1205.59 ton C ha-1 in degraded forest. Allocation of carbon stocks in the standing trees in primary forest, logged over area, secondary forest, and degraded forest were 70, 60, 62, and 7% respectively.